1999
DOI: 10.1046/j.1523-1755.1999.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of membrane composition and structure on solute removal and biocompatibility in hemodialysis

Abstract: Effect of membrane composition and structure on solute removal and biocompatibility in hemodialysis. Significant changes in extracorporeal membranes have occurred over the past five decades in which hemodialysis (HD) has been available as a therapy for both acute renal failure (ARF) and end-stage renal disease (ESRD). For cellulosic membranes, these changes have included a reduction in thickness, hydroxyl group substitution, and an increase in pore size. These modifications have resulted in enhanced efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(101 citation statements)
references
References 56 publications
3
97
0
1
Order By: Relevance
“…This results in a large number of potential binding sites for amikacin adsorption. In contrast, the walls of polyamide fibers have a thin internal "skin" layer and, adjacent to the skin, a sponge-like layer with pores that become larger as they radiate outwards (6). After the ultrafiltrate is formed by the passage of fluid across the skin layer, it may preferentially pass through the pores, with the result that the amikacin contained in the ultrafiltrate will be exposed to only a limited number of binding sites (i.e., those lining the pores).…”
Section: Vol 52 2008 Adsorption Of Amikacin By Hemofilters 1011mentioning
confidence: 99%
“…This results in a large number of potential binding sites for amikacin adsorption. In contrast, the walls of polyamide fibers have a thin internal "skin" layer and, adjacent to the skin, a sponge-like layer with pores that become larger as they radiate outwards (6). After the ultrafiltrate is formed by the passage of fluid across the skin layer, it may preferentially pass through the pores, with the result that the amikacin contained in the ultrafiltrate will be exposed to only a limited number of binding sites (i.e., those lining the pores).…”
Section: Vol 52 2008 Adsorption Of Amikacin By Hemofilters 1011mentioning
confidence: 99%
“…Previous research also showed that ultrafiltration rate per unit area of the membrane that is termed as ultrafiltration flux is roughly proportional to fourth power of mean pore radius of the membrane. Thus by making small variation in the pore size water permeability increase largely [21]. So AAO membrane with uniformly ordered pores have better efficiency as compare to unordered porous polysulfone membrane.…”
Section: Figure 8 Digital Camera Image Of Hemodialyzing Setupmentioning
confidence: 99%
“…Another aspect is the removal of cytokines and other inflammatory markers (lipopolysaccharide fragments, granulocyte inhibitory proteins 1 and 2, IL-1, TNF-) and complement factors (C3a, C5a) by the hemodialysis procedure as well as the adsorption of substances to the hydrophobic high-flux membrane (e.g. factor D) (Clark et al 1999;Schindler et al 2006). Dialysis can reduce leukocyte-endothelial interactions and impair transmigration (Thylen et al 1997).…”
Section: Patients On Hemodialysismentioning
confidence: 99%
“…High-flux dialysis membranes decrease the levels of the two degranulation inhibitory proteins (angiogenin and complement factor D), which could contribute to the maintained respiratory burst and phagocytic capacity seen in patients on high-flux hemodialysis (Horl 2002). There are several molecules, mainly middle-sized molecules, that are cleared to a greater extent by convective therapies, such as hemofiltration or hemodiafiltration (Clark et al 1999). Postdilution hemofiltration was the first convective therapy used, and this method provides a high clearance of middle-and large-sized molecules but a lower clearance of small molecules.…”
Section: Patients On Hemodialysismentioning
confidence: 99%